RESEARCH OF THE VARIATION OF FIRMNESS OF POINTED DRILLS BY METHOD OF SIMULATION MODELING OF PROCESS OF WEAR - Umarov, T.U. (International Journal of Psychosocial Rehabilitation, 2020)
The analytical analysis of flat drills stability variation at opening processing in structural steels is considered. The technique and software for research, of tools stability variation by method of simulation modeling is developed. It is shown that at given modes of processing, average value of stability decreases with ascending of bars hardness variation level. the received expression allows to determine quantity of openings